Ամուսնական զույգի ուղին հայոց հարսանիքում - Զ. Վ. Խառատյան (Հայկական ԽՍՀ գիտությունների ակադեմիա)
Одним из наиболее важных моментов «брачного обмена» в армянской этнической среде является обычай договора между брачующимися сторонами о материальных расходах, связанных со свадьбой. One of the most important moments at the „matrimonial exchange" in the Armenian ethnical environment is the custom of agreement between the matrimonial parties regarding the material exprenses connected with the wedding.
Keywords: History; Ethnography; Geography; Anthropology; Recreation; GT Manners and customs